2021
DOI: 10.1021/acs.jpcc.0c11327
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Ultrafast Charge Carrier Dynamics in Amorphous and Crystalline Sb2Se3 Thin Films

Abstract: The Earth abundant polycrystalline antimony selenide (Sb2Se3) thin film is considered to be a potential photovoltaic material for their appropriate band gap, higher absorption coefficient, and nontoxicity. Interband gap defect states play a major role for efficient solar devices, which depends on the crystallinity of the materials. In the present investigation, we have synthesized an amorphous Sb2Se3 thin film by following the thermal evaporation technique and have also converted the film to crystalline after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 42 publications
1
21
0
2
Order By: Relevance
“…This again confirms the designation of trap states (850 nm for LT and 1200 nm for ST). 38 In the TA spectra of CN/ZIS (Figure 5b), a significant decrease in ESA signal intensity is observed as compared to CN. As we compare the signal intensity for both the region, the ESA II signal is diminished drastically in few tens of ps, while the ESA I signal decays significantly slower in few hundreds of picoseconds.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…This again confirms the designation of trap states (850 nm for LT and 1200 nm for ST). 38 In the TA spectra of CN/ZIS (Figure 5b), a significant decrease in ESA signal intensity is observed as compared to CN. As we compare the signal intensity for both the region, the ESA II signal is diminished drastically in few tens of ps, while the ESA I signal decays significantly slower in few hundreds of picoseconds.…”
mentioning
confidence: 91%
“…Both the signals are fitted with three distinct decay time scales (HSE 0.7 ps, 17.7 ps, and >1 ns; BSE 1.2 ps, 27.7 ps, and >1 ns). The first two time components are assigned to the trapping of charge carriers in short-distance (ST) and long-distance (LT) trap states, respectively 11,38 The final component is associated with the trapping of charge carriers in the deep trap states and eventual recombination. 39,40 These charge trapping processes are schematically discussed in the Supporting Information (Figure S6) Now we have carried out ultrafast TA studies of the CN/ZIS heterostructure after 320 nm pump excitation, and TA spectra are shown in Figure 4a.…”
mentioning
confidence: 99%
“…Transient ultrafast spectroscopic measurements were performed using a setup described in our earlier studies . Briefly, a 80 MHz Ti:sapphire modelock laser, providing pulses at 800 nm, with a typical energy of 500 mW and a 35 fs duration.…”
Section: Methodsmentioning
confidence: 99%
“…The sample was placed in a 2 mm thick cuvette to acquire transient absorption. The acquired data has been analyzed by Surface Xplorer software. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation